Paderewski - Zamoyski, Adam. (Warszawa : Panstwowy Instytut Wydawniczy, 1992)
A biography of the famous Polish pianist, patriot and diplomat.
Originally published in English.
Includes bibliographical references (p. 294-[303]) and index.
Keywords: Paderewski, Ignace Jan, -- 1860-1941.; Musicians -- Poland -- Biography